Perencanaan dan Perancangan Sustainable Food Hub dalam Upaya Mewujudkan Sistem Pangan Berkelanjutan di Kota Denpasar: Sustainable Food Hub - Chrisnantara Marta Putra Marta; I Wayan Wirya Sastrawan; Gde Bagus Andhika Wicaksana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Food security in urban areas is a strategic issue that becomes an important concern in the present and the future, where there are many conditions and factors that affect food security, namely, in terms of production, distribution, consumption which are closely related to the economic, social and political dimensions of society. Denpasar City as the capital of Bali Province which is the center of Balinese life must be able to meet the high food needs of the city community. The Food Hub project was initiated as a city sustainable food system that accommodates aggregation, distribution, production, consumption, education and decomposition activities. The site is located on Jalan Cokroaminoto, North Denpasar, which is the main transportation route for the province, making it easier to access food distribution. Through the literature study stage, the study of precedents of existing facilities at home and abroad. So that results are obtained in the form of specifications for space and users as well as activities that will be carried out in this area, and also how the scheme designed for this facility, both in terms of architecture and meeting the food needs of the city community in a sustainable manner, is implemented through the concept of One Stop Sustainable Food Cycle and its application. green architectural theme that minimizes the impact on the environment. By considering all aspects of architectural design, it is hoped that the Food Hub idea will be able to realize a sustainable food system in Denpasar City.